Impact of Artrolife on hematological, reproductive, and thyroid function in female rats - W. S. A. H. Al-Khafaji; D. A.-H. K. Al-Essawi; N. M. H. Alshabi (Regulatory Mechanisms in Biosystems, 2025)
Artrolife, a widely used nonsteroidal anti-inflammatory drug (NSAID), is commonly administered to alleviate pain, fever and inflammation. This study explored the influence of Artrolife on hematological, reproductive, and thyroid functions in female rats. Twenty adult female rats were randomly assigned to a control group receiving distilled water and to a treatment group administered Artrolife at 0.190 mg/kg body weight daily. After 7 and 20 days, blood samples were collected to assess hematological indices and hormone levels. The results revealed that Artrolife administration led to a noticeable increase in leukocyte count, alongside reductions in erythrocyte count, mean corpuscular volume and mean corpuscular hemoglobin. Furthermore, reproductive hormones such as FSH and LH experienced significant declines, while thyroid hormones displayed marked alterations; T 3 and T 4 levels increased, and TSH levels decreased notably after prolonged treatment. These findings indicate that Artrolife exerts substantial effects on both blood param e ters and endocrine function, potentially disrupting normal physiological balance. The outcomes of this research point to the necessity for further investigations, particularly concerning the long-term implications of Artrolife use in clinical settings.